The assessment: artificial intelligence and financial services. (23rd September 2021) - Bholat, David; Susskind, Daniel
Abstract: : This special issue of the Oxford Review of Economic Policy, based on papers presented at a Bank of England conference, explores the impact of artificial intelligence (AI) on financial services. This opening article provides an overview of AI and its increased use in the financial sector; considers the implications for consumers and competition in the sector; looks at the consequences for central bankers and regulators; and reflects on a more distant world where AI is far more advanced than today. In short, the effect of AI on financial services is likely to be transformative, but that impact remains complex and uncertain.